(untitled) (Dhaka University Journal of Biological Sciences, 2019)
An experiment was carried out to study the effects of calcareousness on phosphate sorption indices of soils using three representative calcareous soils, namely Sara (Aquic Eutrochrept), Gopalpur (Aquic Eutrochrept), and Ishurdi (Aeric Haplaquept) series of Bangladesh. Three non-calcareous soils, namely Belabo (Typic dystrudepts), Sonatala (Aeric Endoaquepts) and Ghatail (Aeric Haplaquept) series were also selected for comparison purposes. Phosphate sorption indices of soils were calculated using Langmuir and Freundlich isotherms. Isotherms were constructed taking one gram of air-dried sieved (< 2 mm) soil into a 50 ml centrifuge tube, and subsequently adding seven initial P concentrations, namely 0, 1, 10, 25, 50, 100 and 150 μg/ml to each centrifuge tube employing a soil/solution ratio of 1 : 20 (w/v). According to the Langmuir equation, the amount of phosphate sorbed followed the order: Sonatala > Ghatail > Sara = Gopalpur > Ishurdi > Belabo. The abundance of amorphous iron rather than the calcareousness was putatively responsible for the high phosphate sorption capacity of soils. Maximum phosphorus buffering capacity (MPBC) of the calcareous soils ranged from 33.4 - 62.8 l/kg. Langmuir and Freundlich equations produced different values for soil P requirements (SPR) at 0.2 and 1.0 mg P/l. Calcareous soils would require 27 - 44 mg P/kg soil to attain 0.2 mg P/l soil solution, which is deemed sufficient for crop growth. The soils would require 32 - 58 mg P/kg soil to reach 1.0 mg P/l soil solution, which is regarded to be safe for soils in terms of susceptibility to P losses. The calculated Langmuir constant b values were higher than the threshold value of 0.07 l/mg for two of the calcareous soils. Therefore, even though the non-calcareous soils sorbed more phosphate, higher bonding energy of P sorption for calcareous soils makes them less vulnerable to loss via surface runoff. Dhaka Univ. J. Biol. Sci. 28(1): 93-110, 2019 (January)